Neuronal Correlates of Cognitive Control Are Altered in Women With Endometriosis and Chronic Pelvic Pain - Steiner, Genevieve Z.; Barry, Robert J.; Wassink, Katherine; De Blasio, Frances M.; Fogarty, Jack S.; Cave, Adele E.; Love, Sapphire; Armour, Mike (Frontiers in Systems Neuroscience, 2020)
Endometriosis is a debilitating women’s health condition and is the most common cause of chronic pelvic pain (CPP). Impaired cognitive control is common in chronic pain conditions, however, it has not yet been investigated in endometriosis. The aim of this study was to explore the neuronal correlates of cognitive control in women with endometriosis. Using a cross-sectional study design with data collected at a single time-point, event-related potentials (ERPs) were elicited during a cued continuous performance test from 20 women with endometriosis (mean age = 28.5 ± 5.2 years) and 20 age- and gender-matched controls (HC) (mean age = 28.5 ± 5.2 years). ERP components were extracted and P3 component amplitudes were derived with temporal principal components analysis. Behavioural and ERP outcomes were compared between groups and subjective pain severity was correlated with ERP component amplitudes. No significant behavioural differences were seen in task performance between the groups (all p > .094). Target P3b (all p < .034) and SW (all p < .040), and nontarget early P3a (eP3a; all p < .023) and late P3a (lP3a; all p < .035) amplitudes were smaller for the endometriosis compared to the HC group. Lower nontarget eP3a (p < .001), lP3a (p = .013), and SW (p = .019) amplitudes were correlated with higher pain severity scores. Findings suggest that endometriosis associated CPP is linked to alterations in stimulus-response processing and inhibitory control networks, but not impaired behavioural performance, due to compensatory neuroplastic changes in overlapping cognitive control and pain networks.